Metformin attenuates V-domain Ig suppressor of T-cell activation through the aryl hydrocarbon receptor pathway in Melanoma: In Vivo and In Vitro Studies - Fawaz E. Alanazi; Homood M. As Sobeai; Khalid Alhazzani; Abdullah Al-Dhfyan; Musaad A Alshammari; Moureq Alotaibi; Khaled Al-hosaini; Hesham M. Korashy; Ali Alhoshani (Elsevier, 2022)
Melanoma is an aggressive skin cancer with a high rate of metastasis to other organs. Recent studies specified the overexpression of V-domain Ig suppressor of T-cell activation (VISTA) and Aryl Hydrocarbon Receptor (AHR) in melanoma. Metformin shows anti-tumor activities in several cancer types. However, the mechanism is unclear. This study aims to investigate the inhibitory effect of metformin on VISTA via AHR in melanoma cells (CHL-1, B16) and animal models. VISTA and AHR levels were assessed by qPCR, Western blot, immunofluorescence microscope, flow cytometry, and immunohistochemistry. Here, metformin significantly decreased VISTA and AHR levels in vitro and in vivo. Furthermore, metformin inhibited all AHR-regulated genes. VISTA levels were dramatically inhibited by AHR modulations using shRNA and αNF, confirming the central role of AHR in VISTA. Finally, melanoma cells were xenografted in C57BL/6 and nude mice. Metformin significantly reduced the tumor volume and growth rate. Likewise, VISTA and AHR-regulated protein levels were suppressed in both models. These findings demonstrate for the first time that VISTA is suppressed by metformin and identified a new regulatory mechanism through AHR. The data suggest that metformin could be a new potential therapeutic strategy to treat melanoma patients combined with targeted immune checkpoint inhibitors.